Self-Immobilized Putrescine Oxidase Biocatalyst System Engineered with a Metal Binding Peptide - Kamathewatta, Nilan J B (Langmuir : the ACS journal of surfaces and colloids, 2020)
Flavin oxidases are valuable biocatalysts for the oxidative synthesis of a wide range of compounds, while at the same time reduce oxygen to hydrogen peroxide. Compared to other redox enzymes, their ability to use molecular oxygen as an electron acceptor offers a relatively simple system that does not require a dissociable coenzyme. As such, they are attractive targets for adaptation as cost-effective biosensor elements. Their functional immobilization on surfaces offers unique opportunities to expand their utilization for a wide range of applications. Genetically engineered peptides have been demonstrated as enablers of the functional assembly of biomolecules at solid material interfaces. Once identified as having a high affinity for the material of interest, these peptides can provide a single step bioassembly process with orientation control, a critical parameter for functional immobilization of the enzymes. In this study, for the first time, we explored the bioassembly of a putrescine oxidase enzyme using a gold binding peptide tag. The enzyme was genetically engineered to incorporate a gold binding peptide with an expectation of an effective display of the peptide tag to interact with the gold surface. In this work, the functional activity and expression were investigated, along with the selectivity of the binding of the peptide-tagged enzyme. The fusion enzyme was characterized using multiple techniques, including protein electrophoresis, enzyme activity, and microscopy and spectroscopic methods, to verify the functional expression of the tagged protein with near-native activity. Binding studies using quartz crystal microbalance (QCM), nanoparticle binding studies, and atomic force microscopy studies were used to address the selectivity of the binding through the peptide tag. Surface binding AFM studies show that the binding was selective for gold. Quartz crystal microbalance studies show a strong increase in the affinity of the peptide-tagged protein over the native enzyme, while activity assays of protein bound to nanoparticles provide evidence that the enzyme retained catalytic activity when immobilized. In addition to showing selectivity, AFM images show significant differences in the height of the molecules when immobilized through the peptide tag compared to immobilization of the native enzyme, indicating differences in orientation of the bound enzyme when attached via the affinity tag. Controlling the orientation of surface-immobilized enzymes would further improve their enzymatic activity and impact diverse applications, including oxidative biocatalysis, biosensors, biochips, and biofuel production